Efektivitas Plester Luka Pada Aplikasi Penutup Luka Insisi Pasca Operasi (EFFECTIVENESS OF WOUND PLASTER FOR COVERING POST-SURGERY INCISION WOUND) - Mustika, Deska Gilang; Kardena, I Made; Pemayun, I Gusti Agung Gde Putra (Buletin Veteriner Udayana; Vol. 7 No. 2 Agustus 2015, 2015)
A study on the difference of wound incision healing in mice (Ratus novergicus) between the wound covered with a plaster compared to the wound that was closed using simple interruptedsutures in terms of macroscopic and microscopic observation has been done. A total of 16 malewhite rats with a weight range of 200 gram randomly divided into two groups. Incision was madeinto linea alba to both group. Incision at linea alba was closed with simple interupted suture, and subcutan was closed with subcutaneous suture using vicril 4/0. The first group of the skin incisionclosed with wound plaster, while the second group the incision is closed with simple interruptedsutures using non-absorbable thread. Results showed that no difference was observed between thewound that covered with plaster compared to the wound that closed with simple interruptedsutures. However, there was a significant difference on the density of collagen in microscopicexamination.
Keywords: incision wound, wound plaster, post-surgery